Quality of Life Outcomes for Bladder Cancer Patients Undergoing Bladder Preservation with Radiotherapy - Feuerstein, Michael A.; Goenka, Anuj (Current urology reports, 2015)
For patients with muscle-invasive bladder cancer, the decision to undergo radical cystectomy or bladder preservation treatment must incorporate survival differences, toxicity, and quality of life. Our objective was to review patient-reported outcomes for bladder preservation treatment with a focus on patients eligible for radical cystectomy, for whom a comparison of patient-reported outcomes is most relevant. Peer-reviewed, English-language manuscripts in MEDLINE and PubMed databases were examined from 1996 through 2014. Subject headings included quality of life, bladder cancer, bladder sparing, bladder preservation, radiation, and radiotherapy. Prospective and retrospective studies of patient-reported outcomes in patients undergoing bladder preservation with radiotherapy for muscle-invasive bladder cancer were included. Two prospective studies and four retrospective studies were identified. Several weaknesses from these studies were identified including small sample sizes, variable time points of assessment, variation in treatment regimens, and failure to use validated or condition-specific questionnaires. From the available data, bladder preservation appears to result to similar or better general quality of life compared to radical cystectomy with satisfactory urinary and sexual function reported in most series. In general, bladder preservation resulted in more gastrointestinal symptoms than radical cystectomy. This is one of the first reviews on the subject of patient-reported outcomes for bladder preservation in muscle-invasive bladder cancer. Although the data are limited, this review may provide a framework for developing well-designed, prospective comparisons of treatment for this patient cohort.